Effective Scheduling Algorithm and Scheduler Implementation for use with Time-Triggered Co-operative Architecture - Kuankid, S.; Aurasopon, A.; Sa-Ngiamvibool, W. (Elektronika ir Elektrotechnika, 2014)
Time-triggered Co-operative (TTC) scheduler provides a simple and reliable operating environment that matches precisely the needs for use in safety-related applications. However, in the design and implementation phases, such scheduler may be suffered from several failure modes that are the fragility of scheduler and the impact of task jitter. The main contribution of this paper is to address the need for an effective scheduling algorithm and scheduler implementation to assure that the TTC can be executed appropriately without an impact on the timing behavior in the system. The paper has developed an algorithm called “TTSA-MTI” to automate the process of scheduling TTC-MTI scheduler which is designed based on the employment of “Sandwich Delay” mechanisms and technique of “Multiple Timer Interrupt”. The results show that the proposed algorithm can help in a significant reduction of computation time and achieve better performances in task release jitter as opposed to a related scheduler. In conclusions, the paper indicates that TTSA-MTI algorithm is an effective task scheduling for use with a range of TTC architecture. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7282